Impaired endothelial glycocalyx predicts adverse outcome in subjects without overt cardiovascular disease: a 6-year follow-up study. (14th October 2021) - Ikonomidis, I; Thymis, J; Simitsis, P; Katsanos, S; Triantafyllou, C; Kousathana, F; Pavlidis, G; Kountouri, A; Polyzogopoulou, E; Katogiannis, K; Vlastos, D; Kostelli, G; et al.
Abstract: Aim: Endothelial glycocalyx is involved in the clinical course of atherogenesis. The purpose of this study was to investigate whether disturbance of glycocalyx integrity is related with increased cardiovascular risk. Methods: Perfused Boundary Region (PBR), a marker of glycocalyx integrity, was measured non-invasively in sublingual microvessels with a diameter ranging from 5–25 μm using a dedicated camera (Sideview, Darkfield Imaging). Increased PBR indicates reduced glycocalyx thickness. We measured baseline PBR in 400 apparently healthy subjects, without established cardiovascular disease. We prospectively monitored the occurrence of major cardiovascular events (MACE-death, myocardial infarction, stroke and heart failure hospitalization) during a 6-year follow-up period using electronic records and clinic visits. Results: Forty-three MACE were documented during follow-up. Subjects with PBR at 5–9 μm microvessel diameter greater than 1.15 μm (mean value of the study cohort) had 2-fold higher risk for MACE than those with lower PBR in a model including sex, age, hyperlipidemia, diabetes, hypertension, current smoking, family history of coronary artery disease and treatment with ACEi/ARBs or lipid lowering agents (hazard ratio (HR): 2.49; 95% CI: 1.23–5.02, p=0.011, net reclassification improvement (NRI): 25%; C-statistic: 0.738). PBR5-9 ≥1.15 was an independent and additive predictor of outcome when added in a model including SCORE, risk factors not included in SCORE (diabetes, family history of CAD) and medication (HR: 2.48 NRI: 23.8%, C-statistic increase from 0.629 to 0.678, for all cardiac events and HR: 4.19, NRI: 33.1%, C-statistic increase from 0.654 to 0.734 for death myocardial infarction and stroke, p<0.01). Conclusion: Endothelial glycocalyx integrity is an independent and additive predictor to atherosclerotic risk factors for adverse outcome at 6 years follow-up in individuals without diagnosed cardiovascular disease. FUNDunding Acknowledgement: Type of funding sources: None.